Explicating ways of consensus-making in science and society: distinguishing the academic, the interface and the meta-consensus - Kosolosky, Laszlo; Van Bouwel, Jeroen (Experts and consensus in social science, 2015)
In this paper, we shed new light on the epistemic struggle between establishing consensus and acknowledging plurality, by explicating different ways of consensus-making in science and society and examining the impact hereof on their field of intersection, i.e. consensus conferences (in particular those organized by the National Institute of Health). We draw a distinction between, what we call, academic and interface consensus, to capture the wide appeal to consensus in existing literature. We investigate such accounts - i.e. Solomon (2007), Beatty & Moore (2010) and Miller (2013) as to put forth a new understanding of consensus-making, focusing on the meta-consensus. We further defend how (NIH) consensus conferences enable epistemic work, through demands of epistemic adequacy and contestability, contrary to the claim that consensus conferences miss a window for epistemic opportunity (Solomon, 2007). Paying attention to this dynamics surrounding consensus, moreover allows us to illustrate how the public understanding of science and the public use of the ideal of consensus could be well modified.